Thermal radiation on mixed convection heat and mass transfer over a vertical permeable stretching/shrinking sheet with Soret and Dufour effects - Dzulkifli, Nor Fadhilah; Bachok @ Lati, Norfifah; Yacob, Nor Azizah; Md Arifin, Norihan; Rosali, Haliza; Pop, Ioan (Springer, 2022)
The flow characteristics of heat and mass transfer on mixed convection over a vertical permeable stretching/shrinking sheet in the presence of thermal radiation with Soret and Dufour effects were studied. The governing equations were transformed to ordinary differential equations using appropriate similarity variables and solved numerically using MATLAB ‘bvp4c’ residual method. The effect of different pertinent flow parameters on velocity, temperature, and concentration distributions were examined and presented graphically. Also, the skin-friction coefficient, heat and mass transfers coefficients were computed for different parameters. The conclusion is drawn that the flow field and other quantities of physical interests are significantly influenced by these parameters. The stability analysis is also conducted due to appearance of dual solutions.